The growing disconnect between food prices and wages in Europe: cross-national analysis of food deprivation and welfare regimes in twenty-one EU countries, 2004-2012. - Reeves, A; Loopstra, R; Stuckler, D (Cambridge University Press, 2017)
OBJECTIVE: Food insecurity has been rising across Europe following the Great Recession, but to varying degrees across countries and over time. The reasons for this increase are not well understood, nor are what factors might protect people's access to food. Here we test the hypothesis that an emerging gap between food prices and wages can explain increases in reported inability to afford protein-rich foods and whether welfare regimes can mitigate its impact. DESIGN: We collected data in twenty-one countries from 2004 to 2012 using two databases: (i) on food prices and deprivation related to food (denoted by reported inability to afford to eat meat, chicken, fish or a vegetarian equivalent every second day) from EuroStat 2015 edition; and (ii) on wages from the Organisation for Economic Co-operation and Development 2015 edition. RESULTS: After adjusting for macroeconomic factors, we found that each 1 % rise in the price of food over and above wages was associated with greater self-reported food deprivation (β=0·060, 95 % CI 0·030, 0·090), particularly among impoverished groups. However, this association also varied across welfare regimes. In Eastern European welfare regimes, a 1 % rise in the price of food over wages was associated with a 0·076 percentage point rise in food deprivation (95 % CI 0·047, 0·105) while in Social Democratic welfare regimes we found no clear association (P=0·864). CONCLUSIONS: Rising prices of food coupled with stagnating wages are a major factor driving food deprivation, especially in deprived groups; however, our evidence indicates that more generous welfare systems can mitigate this impact.